A Single DC Source Generalized Switched Capacitors Multilevel Inverter with Minimal Component Count - Kasinath Jena; Dhananjay Kumar; B. Hemanth Kumar; K. Janardhan; Arvind R. Singh; Raj Naidoo; Ramesh C. Bansal (International Transactions on Electrical Energy Systems)
This paper presents a new single-source switched capacitor- (SC-) based multilevel inverter (MLI) design with a boosting potential of three times the supply voltage. To produce a waveform with seven output voltage levels, the suggested switching capacitor inverter consists of eight switches, single diode, and two capacitors. Because capacitors are inherently balanced, there is no need for a balancing circuit or sensor. The structure can be expanded using the provided generalized equations. In addition, the technique for switching control and loss analyses is explored. A fair comparison with the most recent SCMLI topologies has been conducted to demonstrate the merits of the proposed work. Furthermore, the proposed topology is evaluated using the MATLAB/SIMULINK tool, and experiments under both transient and steady-state situations are performed to demonstrate its feasibility. At dynamic-loaded situations, the performance of the proposed SCMLI with dynamic modulation index and switching frequency is tested.